The Efficacy of Garlic in Alleviating Fluoranthene and Pyrene Induced Pulmonary Injury in Rats - Ismail, Teh Rasyidah (2003)
Amongst polycyclic aromatic hydrocarbons (PAH) found during the Malaysian 1997 haze episode were fluoranthene (FL) and pyrene CPY). In manifest of evolving strategies and bringing about an attenuation of deleterious effects of these particles in human, both acute symptoms and chronic inflammation of pulmonary system were studied in rats. The acute exposure studies were performed to determine presence of apoptosis and proteases activity in the lung of rats following treatment with FL, PY and FL+PY. Rats not receiving any treatment served as controls while those administered with FL PY and FL+PY were instilled intratracheally at the dose of 11ng, 11.5ng and combination of both doses respectively. All rats were euthanised at 1, 8 and 24 hours post-instillation (p.i). Apoptosis estimation was made on haematoxylin-eosin stained histopathologic sections, terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling (TUNEL) analysis and DNA laddering of lung samples. As for protease analyses, total protein content measured by using BSA kit, elastase-like activity and neutrophil elastase activity were performed in the lung lavage collected from rats. Different phases of apoptosis were discovered in the pneumocytes and bronchial epithelium of lung samples of all PAH -treated rats. The histopathological finding showed that there was increment of apoptotic cells (p<O.05) with advancement of time, especially in 8 and 24 hours p.i. This was also confirmed by TUNEL analysis and DNA laddering. The obtained data showed a time-dependent increase in lung lavage total protein content elastase-like activity and neutrophil elastase activity. The chronic exposure studies were conducted as described in the acute study but for a three month period. However, an assessment was also made on the efficacy of garlic as an alternative therapeutic agent against FL and PY effects. Rats from the control, FL, PY and FL+PY groups were daily fed on a commercial basal diet while rats from the garlic (G), FL+G, PY+G and FL+PY+G groups were fed the basal ration containing garlic powder incorporated at the rate of 80mg/kg body weight/rat/day. The outcome demonstrated morphological alteration and growth disorder in pneumocytes and bronchial epithelium of rats from all PAH-treated groups. The PAH-treated groups also showed dreadful effects in proteases activities, levels of IgG, IgA, alveolar macrophages activities and glutathione-S-transferase in the lung. In contrast, all PAH-treated groups fed with garlic showed significant improvement in pathological changes, proteases activities, immunology, and enzyme activity in the lung. Concisely, environmental hazard of FL, PY and their combination to lung of rats as target organs triggers deleterious changes either by acute or chronic exposure while garlic has tremendous potential in alleviating the chronic effects of FL and PY.